A note on almost anti-periodic functions in Banach spaces - Marko Kostic, Daniel Velinov (Faculty of Science, University of Kragujevac, 2020)
The main aim of this note is to introduce the notion of an almost anti-periodic function in Banach space. We prove some characterizations for this class of functions, investigating also its relationship with the classes of anti-periodic functions and almost periodic functions in Banach spaces.
Keywords: Almost anti-periodic functions, almost periodic functions, anti-periodic functions, Bohr transform, Banach spaces.